A study of assessment of knowledge, attitude and practice of antibiotic stewardship among healthcare providers in a tertiary care hospital of Sangli - Shetti, Santoshkumar A.; Patil, Aditi N.; Magadum, Madhushree S.; Limaye, Ramchandra P.; Pendhari, Shabbir R.; Patil, Pallavi P.; Jagadale, Sachin G. (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Antimicrobials are routinely used for variety of clinical conditions but are also misused leading to drug resistance bacteria in clinical practice. Consultants can gain the knowledge about it and can also have the depth of problem faced, their prescribing behavior mainly depends on their attitude and understanding of condition. Our aim of this study is to evaluate the knowledge and beliefs about antibiotics prescribing among health care workers in a tertiary care hospital of Sangli. Methods: Our present study was conducted in the Bharati hospital, BV (DU) medical college and hospital, Sangli. Ethical clearance from the institutional ethics committee was obtained and it was, cross-sectional questionnaire-based study carried out in the form of a survey in which a pretested, semi-structured, validated questionnaire was provided to junior residents, senior residents and faculty of different specialties and responses were recorded. Questionnaire comprises of 9 in knowledge, 10 in attitude and 10 in practice section. Results: Out of all participants 84.5% believed that no need of antibiotics for running and blocked nose. Majority 89.6% were expressed that sample culture should be sent before starting antibiotics. 90.4% participants believed that education of patients will help. Only 76.8% strictly adhere to the antibiotic policy of our hospital. Conclusions: The present study on antibiotic usage gives useful information about the knowledge, attitudes and practices of prescribers and help plan suitable educational modifications that aim at improving the antimicrobial prescribing and minimizing the development of drug resistance in our developing country.